(untitled) (Research, Society and Development, 2021)
Considering the massive litigation that, in addition to congesting the Judiciary Power, generates legal uncertainty through conflicting decisions on the same issue of law, Law n. 13.105/2015 introduced into the Brazilian procedural legal system mechanisms and techniques designed to ensure stability, coherence and integrity to the jurisdictional system. Among them, the Institute of Repetitive Claims Resolution Incident - IRDR, with the objective of promoting legal certainty and equal treatment to the lawsuits that deal with the same question of law. Furthermore, a microsystem for the judgment of repetitive causes was created, comprising the IRDR and repetitive special and extraordinary appeals. This research seeks to demonstrate the relevance of the IRDR to the Brazilian procedural order, to point out points of doctrinal divergence and the general rules that make up the microsystem for judging repetitive cases. Therefore, the deductive method of scientific investigation was used, with data collection through bibliographic research in textbooks, articles, scientific journals, legislation, jurisprudence and doctrines.